2001
DOI: 10.2118/74702-pa
|View full text |Cite
|
Sign up to set email alerts
|

Scaling of Cocurrent and Countercurrent Capillary Imbibition for Surfactant and Polymer Injection in Naturally Fractured Reservoirs

Abstract: Summary This study tests the existing capillary imbibition scaling formulations in literature and proposes modifications to them for surfactant- and polymer-injection applications. Laboratory tests were performed using Berea Sandstone cores with different shapes, sizes, and boundary conditions. Kerosene, engine oil, mineral oil, and crude oil were selected as the oleic phase. Brine and two different concentrations of surfactant and polymer solutions were the aqueous phases. The capillary imbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(41 citation statements)
references
References 22 publications
0
41
0
Order By: Relevance
“…Hamon and Vidal (1972) performed four one-dimensional water-oil COCSI tests on synthetic water-wet porous media with different heights to study the effect of block height on imbibition. Babadagli et al (1999) and Babadagli (2001) claimed doing pure COCSI experiments. However, the boundary conditions used in their experiments reveal that those tests were mainly COUCSI with some minor cocurrent productions.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Hamon and Vidal (1972) performed four one-dimensional water-oil COCSI tests on synthetic water-wet porous media with different heights to study the effect of block height on imbibition. Babadagli et al (1999) and Babadagli (2001) claimed doing pure COCSI experiments. However, the boundary conditions used in their experiments reveal that those tests were mainly COUCSI with some minor cocurrent productions.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Surfactant solutions are expected to change capillary imbibition performance on sandstone and chalky carbonates (Keijzer and de Vries, 1990;Al-Lawati and Saleh, 1996;Alveskog et al, 1998;Babadagli et al, 1999;Spinler, 2000;Babadagli, 2001Babadagli, , 2002Babadagli, , 2003. This change could be due to lowered IFT or change of the wettability from oil-to water-wet.…”
Section: Static Imbibition Experimentsmentioning
confidence: 99%
“…It is important to characterize the fluid flow during spontaneous imbibition in order to establish the relationship between production rate and time. Many researchers have studied the spontaneous imbibition in porous media (Aronofsky et al 1958;Du Prey 1978;Hamon and Vidal 1986;Reis and Cil 1993;Cuiec et al 1994;Al-Lawati and Saleh 1996;Zhang et al 1996;Babadagli (2001) ;Høgnesen et al 2004;Tavassoli et al 2005). In this study, we reviewed many models reported in the literature and proposed a fractal model to predict the spontaneous imbibition rate by considering the rock's property represented by fractal dimension.…”
Section: Introductionmentioning
confidence: 99%